Digital teaching resource management system for higher education - Lin Zhu; Li Zhuang; Caihong Li (Engineering Reports)
Abstract At present, the management and utilization of teaching resources in higher education are characterized by issues, such as limited functionality, simple structure, inadequate sharing, and weak management capacity. To address these challenges, this study proposes a multimedia information processing technique based on computer technology. The system utilizes Java programming language, the Spring Boot framework, Servlet, and other technologies to process data through a MySQL database. It consists of main modules for students, teachers, and administrators. The developed digital teaching resource management system is stable, user‐friendly, with a clear interface, and capable of meeting the educational needs of colleges and universities. By maximizing the sharing and integration of university teaching resources, this system not only innovates teaching and learning approaches but also holds significant practical implications.